IMPLEMENTASI PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR M.HH.02.UM.06.04 TAHUN 2011 TENTANG PEDOMAN PELAYANAN KESEHATAN DI LINGKUNGAN KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DI LEMBAGA PEMASYARAKATAN KELAS IIB PASIR PENGARAIAN - Faradila, Mutia; Firdaus, Emilda; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Health care is a form of realization of the implementation of human rights and is one ofthe elements of welfare that must be realized in accordance with the ideals of the Indonesiannation. All citizens have the right to obtain health services. Article 4 of Law Number 36 of 2009concerning health says "everyone has the right to health".This type of research is sociological or empirical juridical legal research, namelyresearch obtained directly from the community or primary data research. This research aims tosee the correlation between legal regulations and their implementation in the community byinstitutions.Based on the results of temporary research, the implementation of the MinistryRegulation has not been as expected. This is due to limitations in facilities and infrastructure andthe unavailability of health workers at the Pasir Pengaraian Class IIB Penitentiary. Healthservices in its implementation have been carried out in collaboration with the local CommunityHealth Center in the form of health service visits 2 (two) times a week and there is a PrimaryClinical Clinic at the Pasir Pengaraian Class IIB Correctional Institution, but in its enforcementit is still not appropriate and must be adjusted to the Regulation of the Minister of Law andHuman Rights Number M.HH.02.UM.06.04 of 2011 concerning Guidelines for Health Serviceswithin the Ministry of Law and Human Rights.Keywords: Health Services, Correctional Institution, Human Rights